EFFECTS OF SKILLS-BASED INSTRUCTIONAL APPROACH ON PRE-SERVICE TEACHERS’ LESSON PLAN DELIVERY SKILLS AND PUPILS’ BASIC LITERACY IN SOUTH-WEST, NIGERIA (Unilorin Journal of Lifelong Education, 2025)
In teacher education, there appears to be a methodology gap between the methodology courses designed for basic education pre-service teachers in colleges of education and the basic education curriculum at the primary schools/adult learning centers in Nigeria. The didactic teaching narrative of training basic education teachers is no longer acceptable for basic literacy classroom practice in the 21st century. Hence, this study was carried out to change the narrative by introducing skills-based instructional approach and examining its effects on preservice teachers’ literacy lesson plan delivery skills and primary school pupils’ learning achievement in south-west, Nigeria. A total sample size of 80 pre-service teachers and 185 primary school pupils, drawn from three south-west states, namely Ogun, Ondo and Oyo states participated in the study. Three hypotheses were formulated and tested at 0.05 level of significance with the aid of four different instruments for data collection. The study adopted a pre – test, post – test, control group, quasi-experimental design with a 2x2x2 factorial matrix. Analysis of Covariance (ANCOVA) was adopted for data analysis, while Sidak post-hoc analysis was used to show any significant difference between the experimental and the control groups. The results of the study revealed among other things that after adjusting for the covariance, the effect of treatment on literacy lesson plan delivery skills was statistically significant. The difference between the experimental group and the control group was also found to be significant. Similarly, the effects of treatment on pupils’ learning achievement in Reading and Writing were also found to be statistically significant